Population density of Pachyoliva columellaris (G. B. Sowerby I, 1825) (Mollusca, Gastropoda) in a sandy beach from province of Manabí, Ecuador - Minchala, Michelle (2025)
Pachyoliva columellaris (G. B. Sowerby I, 1825) is a snail species common in the intertidal zone of sandy beaches. The objective of this study was to determine its population density and size frequency distribution on the beach between Punta Blanca and Punta Prieta, Province of Manabí. Sampling was carried out between June and July 2023, during low tide, through linear transects parallel to the coast, arranged in two strata (lower and upper). Samples were collected with a shovel 25 cm wide and 20 cm long, sieved with a 1 mm mesh. In each sample, the number of P. columellaris individuals was counted and their lengths (shell length, LH in Spanish) were recorded using a millimetric paper. Population density was highly variable, with significant differences between transects and an average of 11 ind./500 cm2. Population densities were similar between strata. Size frequency distributions of P. columellaris showed two main modes for the total data (5.71 mm LH and 9.91 mm LH), lower (6.44 mm LH and 9.79 mm LH) and upper strata (5.40 mm LH and 9.94 mm LH). The modes showed that small individuals (< 8 mm LH) preferred the upper strata and large individuals (< 8 mm LH) preferred the lower strata. Population densities of P. columellaris are highly variable due to population changes associated with tidal dynamics. Comparisons between studies should be made with caution due to methodological differences.